PENERAPAN PEMBELAJARAN STEM UNTUK ANAK USIA DINI - Sitti Muliya Rizka; Dara Rosita; Maya Safhida (Universitas Syiah Kuala, 2021)
The issue of the existence of the technological revolution 4.0 a mid Indonesian society, especially Aceh, encouraged educators to continue to transform the education system. It is, of course, related to the challenges of teachers' readiness, including early childhood teachers, in shaping a smart and intelligent generation of Aceh in the global industrial era 2045. In the future, each generation of Aceh will become a public need and is expected to be able to compete from all sides of life both locally and internationally. With the rapid development of appropriate technology in education, the skills of early childhood teachers are needed in modifying learning. Thus, it can sharpen the mind of students in the fields of science, technology, language, and art. Based on today's data, education in Aceh is left behind than that of other regions in Indonesia. This is far from reality and expectation of the motto